IMPLEMENTASI DAKWAH NAFSIAH PERSPEKTIF AL-QUR’AN DAN HADIS DENGAN METODE PARTISIPATORIS DI KELURAHAN KATANGKA KECAMATAN SOMBA OPU KABUPATEN GOWA - Muliaty Amin (Fakultas Dakwah dan Komunikasi, 2016)
This study examines and answer the main problem of da’wa Nafsiah perspective of the Qur'an and hadith that its implementation in the form of da’wa village level participatory in Katangka Somba Opu District Gowa. As a sub problems examined is how the implementation of da'wa Nafsiah with participatory models according to the Quran and Hadith, as well as constraints and solutions in Sub Katangka In n Somba Opu District Gowa. The method used, referring to the field research, the approach is multidisciplinary. Sources of data obtained from field research through observation and interviews. The results of the study concludes that the mission Nafsiah with participatory models in Sub Katangka done well and is relevant to the concept of propaganda based on the Qur'an and Hadith. It can be seen the situation of local communities continue to perform its obligations especially fard prayers and practices of the other. In the meantime, the call Nafsiah in Sub Katangka basically still have kendalan, but this does not become a significant constraint and therefore recommended that a model of participatory Nafsiah propaganda in the Village Katangka always strived to be realized.